Anykščiai St. Matthew Parish at the Beginning of 17th – 18th c. - Kamuntavičienė, Vaida (History / Istorija, 2020)
Abstract. Te article reveals the situation of the parish of St. Matthew in Anykščiai in the 17th century, presents data about the church, describes the altars, the pastoral activities of the clergy, and shows the relations of the population with the parish. One case study gives an insight into the functioning of the Catholic Church in the Grand Duchy of Lithuania. Te research is carried out using unpublished documents of Anykščiai parish, such as the visit of 1678 and others, which have not been included in scientifc circulation so far.